Post occupancy evaluation of space energy intensity on green building index energy efficiency (EE) criteria - Yaman, Rostam; Abdullah, Jamalunlaili; Adnan, Hamimah; Ismail, Farrah Zuhaira; Ahmad, Noraini (Faculty of Engineering, Chulalongkorn University, 2021)
Green interior tool sustainable benchmarking system in Malaysian is relatively new. Despite of the launch of Malaysian Green Building Councils very own Green Interior Tools (GBI-IT) and implementation, there is still deficiency in post-occupancy measure being conducted in evaluating the holistic sustainability level on the post-certified interior project. The lacking is in particular related to the Space Energy Intensity (SEI). Thus, embark the study problem whether the certified project sustainability level is in accord to pre-occupancy rating score as parallel to vision by the designers upon occupation, in particular on Energy Efficiency (EE). The study objectives is to examine the SEI, to identify similarities and discrepancies of SEI and to weigh the main EE sub-criteria which effect SEI in order to enhance continuing sustainable EE after one year occupation. The SEI equation method and implementation approach are conducted in this concept paper by measuring the total space energy consumption per year/interior space area. The study design is devised into three key phases; 1. Content analysis of GBI-IT EE core criteria; 2. Comparative data analysis between post-occupancy and simulated pre-occupancy scoring level and; 3. Evaluation of key EE sub-criteria that affect SEI in order to improve continuing sustainability after occupation. The findings and discussions based on SEI comparative analysis will improve sustainability practice towards continuing sustainable agenda and will facilitate further enhancement for future sustainable approach in interior SEI.